Structural durability assessment of welded offshore K-nodes by different local design concepts - C.M. Sonsino (Fracture and Structural Integrity)
The structural durability design of complex welded structures should not rely only on one single design method but should apply different methods for assuring the reliability of the assessment. In this context the application of the structural stress concept, notch stress concept and crack propagation concept are discussed through the example of K-nodes used in energetic offshore constructions like oil platforms or windpower plants, presenting the state of the art.